Studi Perbandingan Terhadap Rumusan Pidana Mati Pada Kitab Undang Undang Hukum Pidana Dengan Undang Undang Nomor 01 Tahun 2023 Tentang Kitab Undang Undang Hukum Pidana - Aritonang, David Rioland; Ismansyah; Elvandari, Siska (Fakultas Hukum Universitas Andalas, 2024)
There is a comparison the regulation of the formulation of the death penalty between the Indonesian Criminal Code and Law Number 01 of 2023 concerning the Criminal Code. The research method used is normative juridical, which is a research method using library literature, which consists of books, laws, scientific works, and various kinds of library literature. The data sources used are primary, secondary and tertiary legal data. The implementation of the death penalty based on Law No.02/PNPS/1964 concerning the Implementation of the Death Penalty, namely that the death penalty imposed in general justice or military justice is carried out by being shot to death. A comparison of the formulation of the death penalty between the Old Criminal Code and the National Criminal Code is that the death penalty can be changed to life imprisonment if the convict behaves well during the 10 years in prison, the death penalty is no longer included in the basic criminal category and becomes an alternative (special) punishment, the regulation of delaying the death penalty Pregnant women, breastfeeding mothers and mentally ill people are included in the National Criminal Code, the death penalty in the National Criminal Code prioritizes human rights, the regulation of the death penalty in the National Criminal Code is more modern, advanced and follows Indonesian legal culture